1997
DOI: 10.1074/jbc.272.30.18530
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Is a Potent Inhibitor of the Apoptotic Protease, Caspase-3

Abstract: The prevention of apoptosis by Zn2+ has generally been attributed to its inhibition of an endonuclease acting in the late phase of apoptosis. In this study we investigated the effect of Zn2+ on an earlier event in the apoptotic process, the proteolysis of the "death substrate" poly(ADP-ribose) polymerase (PARP). Pretreatment of intact Molt4 leukemia cells with micromolar concentrations of Zn2+ caused an inhibition of PARP proteolysis induced by the chemotherapeutic agent etoposide. Using a cell-free system con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(141 citation statements)
references
References 28 publications
13
128
0
Order By: Relevance
“…The point of convergence of these pathways at the level of eIF4G is most likely the activation of one or more`executioner' caspases (Longthorne and Williams, 1997; Kamada et al, 1997;Cohen, 1997). This is consistent with the ability of the caspase inhibitors (Z-VAD.FMK and Z-DEVD.FMK; Dolle et al, 1994;Fearnhead et al, 1995;Perry et al, 1997;Juo et al, 1997), but not calpain or proteosome inhibitors (data not shown), to block the disappearance of eIF4G regardless of the apoptosis-inducing stimulus.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The point of convergence of these pathways at the level of eIF4G is most likely the activation of one or more`executioner' caspases (Longthorne and Williams, 1997; Kamada et al, 1997;Cohen, 1997). This is consistent with the ability of the caspase inhibitors (Z-VAD.FMK and Z-DEVD.FMK; Dolle et al, 1994;Fearnhead et al, 1995;Perry et al, 1997;Juo et al, 1997), but not calpain or proteosome inhibitors (data not shown), to block the disappearance of eIF4G regardless of the apoptosis-inducing stimulus.…”
Section: Discussionsupporting
confidence: 57%
“…Both Z-VAD.FMK and Z-DEVD.FMK have relatively broad speci®cities against a number of caspases (Kidd, 1998). ZnCl 2 is an inhibitor of caspase-3 but it is not clear whether it is also active against other caspases (Perry et al, 1997). Although it is likely that several di erent caspases become activated under the conditions of our experiments the lack of e ect of ZnCl 2 on eIF4G cleavage might suggest that caspase-3 activity is not required.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Since MT may be involved in zinc homeostasis, it can regulate the supply of zinc to p53 protein for its optimum activity and also protect the cells from toxicity to metals and free radicals. Lastly, zinc is known to inhibit the activation of both caspase 3 (Perry et al, 1997) and Ca/Mg-dependent endonuclease (Cohen and Duke, 1984), which play critical roles in the execution of apoptosis. MT, as a zinc binding protein, may also act as an anti-apoptotic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential element for life and is known to play important roles in biological processes including gene expression, apoptosis, enzyme regulation, immune system and neurotransmission [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%